2016
DOI: 10.17759/chp.2016120318
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating on Facebook: Teachers Exchanging Experiences Through Social Networking Sites

Abstract: This study explores the use of Facebook for educational purposes, as a collaborative online space for enabling communication among teachers from different schools. The article describes how a group of 43 teachers on Facebook, from various schools in the southeast region of Brazil used a group on Facebook as a collaborative space for communicating among each other. On the group, these teachers shared experiences about the use of digital technologies in their secondary education classes. This study is based on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Social media has provided varieties of innovative interaction systems [127,128] and meets the need for instant access to information [129]. These media applications have been found by many studies [124,[130][131][132] as critical contemporary information tools. Attaining a significant presence [133], its impact is indeed impressive; from changing the manner of information access and sharing [134], to improving interaction abilities, engagement and influence [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…Social media has provided varieties of innovative interaction systems [127,128] and meets the need for instant access to information [129]. These media applications have been found by many studies [124,[130][131][132] as critical contemporary information tools. Attaining a significant presence [133], its impact is indeed impressive; from changing the manner of information access and sharing [134], to improving interaction abilities, engagement and influence [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…In a large Korean community, Seo also found that members became motivated to participate in the community after seeking help and being helped by other teachers to return their favor to some other teachers [30]. Likewise, da Cunha Júnior, et al [42] found that, in their longitudinal case study of a Facebook group of 43 teachers, the general low level of participation resulted in no collaboration initiatives among teachers.…”
Section: Social Networkmentioning
confidence: 98%
“…In special interest groups, teachers who share a similar interest can work collaboratively on a smaller scale [41,49,55,56]. In a case study of 43 teachers in a Facebook group, da Cunha Júnior, van Oers and Kontopodis [42] concluded that teachers tended to more critically collaborate in small groups than large groups. To support these groups, members should be able to initiate a collaborative project where they construct a meaningful product that they can actually use and build a closer relationship during collaboration [41,42,55].…”
Section: Design Suggestions For Total Commitmentmentioning
confidence: 99%
See 2 more Smart Citations